Sex-Biased Population Admixture Mediated Subsistence Strategy Transition of Heishuiguo People in Han Dynasty Hexi Corridor - Xiong, Jianxue; Du, Panxin; Chen, Guoke; Tao, Yichen; Zhou, Boyan; Yang, Yishi; Wang, Hui; Yu, Yao; Chang, Xin; Allen, Edward; Sun, Chang; Zhou, Juanjuan; et al. (Frontiers in Genetics, 2022)
The Hexi Corridor was an important arena for culture exchange and human migration between ancient China and Central and Western Asia. During the Han Dynasty (202 BCE-220 CE), subsistence strategy along the corridor shifted from pastoralism to a mixed pastoralist-agriculturalist economy. Yet the drivers of this transition remain poorly understood. In this study, we analyze the Y-chromosome and mtDNA of 31 Han Dynasty individuals from the Heishuiguo site, located in the center of Hexi Corridor. A high-resolution analysis of 485 Y-SNPs and mitogenomes was performed, with the Heishuiguo population classified into Early Han and Late Han groups. It is revealed that: 1) when dissecting genetic lineages, the Yellow River Basin origin haplogroups (i.e. Oα-M117, Oβ-F46, Oγ-IMS-JST002611, and O2-P164+, M134-) reached relatively high frequencies for the paternal gene pools, while haplogroups of north East Asian origin (e.g. D4 and D5) dominated on the maternal side; 2) in interpopulation comparison using PCA and Fst heatmap, the Heishuiguo population shifted from Southern-Northern Han cline to Northern-Northwestern Han/Hui cline with time, indicating genetic admixture between Yellow River immigrants and natives. By comparison, in maternal mtDNA views, the Heishuiguo population was closely clustered with certain Mongolic-speaking and Northwestern Han populations and exhibited genetic continuity through the Han Dynasty, which suggests that Heishuiguo females originated from local or neighboring regions. Therefore, a sex-biased admixture pattern is observed in the Heishuiguo population. Additionally, genetic contour maps also reveal the same male-dominated migration from the East to Hexi Corridor during the Han Dynasty. This is also consistent with historical records, especially excavated bamboo slips. Combining historical records, archeological findings, stable isotope analysis and paleoenvironmental studies, our uniparental genetic investigation on the Heishuiguo population reveals how male-dominated migration accompanied with lifestyle adjustments brought by these eastern groups may be the main factor affecting the subsistence strategy transition along the Han Dynasty Hexi Corridor.